Acceptability of Malaysian construction practitioners in adopting 4D - Ali, Maisarah; Mohd Noor, Julia (2012)
The problem of delay in construction industry is a global phenomenon and the construction industry in Malaysia is no exception. In the current day context, despite significant benefits in terms of time and cost savings gained through the systematic use of 4D technologies on construction projects, Malaysia construction industry has yet to embrace this 4D CAD technology. The aim is to explore the acceptability of 4D as a planning and control tool during construction phase of project life cycle. Surveys and semi-structured interviews were carried out on 169 respondents comprising of the clients, local authorities or regulatory bodies, contractors and consultants. The responses obtained indicate that 96.3% acknowledges the application of this new 4D technology as a useful tool with good potential to mitigate delays especially in relation to visualization, analysis and communication during construction. Based on the outcome of the study, it is recommended that financial and technical support be made available before its actual implementation can be realized. Keywords: Malaysian construction industry, 4D, visualization, communication, mitigate delay